Counter-facing plasma guns for efficient extreme ultra-violet plasma light source - Kuroda Yusuke; Yamamoto Akiko; Kuwabara Hajime; Nakajima Mitsuo; Kawamura Tohru; Horioka Kazuhiko (EPJ Web of Conferences, 2013)
A plasma focus system composed of a pair of counter-facing coaxial guns was proposed as a long-pulse and/or repetitive high energy density plasma source. We applied Li as the source of plasma for improvement of the conversion efficiency, the spectral purity, and the repetition capability. For operation of the system with ideal counter-facing plasma focus mode, we changed the system from simple coaxial geometry to a multi-channel configuration. We applied a laser trigger to make synchronous multi-channel discharges with low jitter. The results indicated that the configuration is promising to make a high energy density plasma with high spectral efficiency.